Analisis Peran Teknologi Dalam Proses Pemilihan Umum Daerah - Mayang Tyas Nur Istikomah (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
The role of information technology in the regional general election process is increasingly important in creating transparent, efficient and accountable elections. This research discusses how information technology, such as e-Voting, e-Recapitulation, and the Election Information System (SIP), has been implemented to support various stages of elections, starting from voter registration, campaigning, voting, to calculating results. In addition, an analysis was carried out on emerging challenges in terms of cyber security, public trust and uneven technological infrastructure. The research results show that the use of technology can increase the efficiency of the election process and minimize the potential for fraud, but also requires serious attention in developing regulations and human resource readiness. This study emphasizes the importance of strengthening digital frameworks and public education to realize more democratic and inclusive regional elections through the application of information technology.